Success of Nonsurgical Endodontically Treated Posterior Teeth with Complex Restorative/Prosthodontic Treatments: A Retrospective Study - Vatankhah , Mohammadreza; Ashraf, Hengameh; Jamalian, Forough; Talebi, Sepehr; Akbrazadeh Baghban, Alireza; Khosravi, Kamyar; Zargar, Nazanin (Iranian Endodontic Journal, 2024)
Introduction: Endodontic therapy has been regarded as a safe treatment option with highly promising results in preserving natural teeth. Numerous factors may influence the longevity of endodontically treated teeth (ETT), thus altering their success/survival rate. This study aimed to determine the survival and success rates of endodontically treated premolars and molars with different complex restorative/prosthodontic treatments. Materials and Methods: A total of 190 patients with an ETT were included, who had received final coronal restoration up to 14 days after the temporary one and at least one year prior to the enrollment. The investigator evaluated the quality of endodontic filling, coronal restoration, mobility, and proximal contacts. Data were analyzed with multiple binary logistic regression and the Chi-Square test. Results: The average duration of follow-up was 28.6±11.9 months. Overall, 89.4% (170/190) of the teeth survived. The overall success rate for the investigated teeth was 70.5% (134/190). Success rates of 100% for crown, 95.7% for post and core crown (PCC), and 94.7% for amalgam build-up with post were achieved. However, the success rates were 75%, 52.5%, and 50% for amalgam build-up, composite build-up, and PCC with crown lengthening, respectively. The Chi-square test revealed that there was a significant difference between the different restorations in terms of success (P<0.001). Multiple binary logistic regression models revealed that coronal leakage (P=0.048), obturation void (P=0.037), obturation length (P=0.020), mobility (P=0.002), type of the restoration (P<0.001), and proximal contact (P<0.001) were significant predictors for success. However, apical lucency, root length, marginal caries, tooth type, and post did not appear to be significant indicators of success (P>0.05). Conclusions: ETT with minimal mobility, exhibiting underfilled obturations without visible voids, and having received crown/PCC/amalgam build-up with a post, along with the presence of both proximal contacts, tend to exhibit a significantly high success rate.